Health Service Process: Lean Six Sigma Concept for Hospitals (Casemix Hospitals) - Sudarwan; Nurohim, Achmad; Sutrisno Hadi, Dominicus; Yanuar Rahmat Syah, Tantri; Angga laksana, Eka (International Journal of Psychosocial Rehabilitation, 2020)
Background-National Health Insurance, whose implementation began in January 2014, made a change in the payment system from the Retrospective Payment System to the Prospective Payment System in INA-CBG rates. The difference in INA-CBG rates and hospital rates is a fundamental problem so hospitals must make efforts to achieve quality and cost control. The purpose of this study was to determine the efforts taken by hospitals related to differences in hospital outpatient service fees and inpatient service rates to INA-CBG’s rates. Method-The research method was carried out quantitatively. Lean consumption is used to analyze the manufacturing sector, namely lean manufacturing rather than industrial processes. In addition, the development of lean consumption in the hospital sector is the right choice to improve the quality of hospital services. Thus, this aims to test the Lean Hospital algorithm by defining, measuring,analyzing, improving, and controlling DMAIC (Define, Measure, Analyze, Improve, Control) and the LCM (Lean Consumption Map) method through hospital services. By using a comparison of the completion time of outpatient and inpatient operational activities. The results showed that the hospital Lean algorithm successfully assessed the comparison method with the Lean Consumption Map and Value-Added Assessment. In this study, we used qualitative research methods and interviews with internal and external correspondence, respectively. Result-We found that the DMAIC application and the Lean Consumption Map in the Lean Hospital algorithm will increase document completion times and service processes at the Hospital.